Spirituality in oncology - a consensus by the Brazilian Society of Clinical Oncology - Toloi, Diego de Araujo; Landeiro, Luciana Castro Garcia; Gadia, Rodolfo; Chaves, Cristiane de Lacerda Gonçalves; Forte, Daniel Neves; Castilho, Rodrigo Kappel; Garcia, João Batista Santos; Andrade, Carlos Jose Coelho de; Gaui, Maria Fátima; Machado, Maria Cecilia Mathias; Mathias, Clarissa (Brazilian Journal of Oncology, 2022)
Spirituality is a dynamic and an intrinsic aspect of humanity and is usually intense in cancer for patients, families, and health care teams. Evidence on spirituality, health, and healing have increased over the last decades. This consensus is for those involved in cancer patient care, with concepts and possible strategies for addressing spirituality, with discussion on the relevance, impact, and challenges of spirituality care. The purpose and intent of the consensus are to highlight the need for spirituality inclusion in the complex and delicate trajectory of cancer patients.
Keywords: Neoplasms; Spirituality; Consensus